Uma análise dos impactos dos instrumentos das políticas monetáir e fiscal sobre a disponibilidade de recursos federais às demais esferas de governo no Brasil - Carvalho, André Pinheiro de (2014)
This work investigates the impact of the instruments of monetary and fiscal policy on the funds raised by the Federal Government and available to other federal entities (cities and states) in Brazil. The dependent variables were the Income Tax (IT), the Tax on Industrialized Products, while controls were the official interest rate (SELIC), the restricted means of payment (M1) and exchange rate (real / U.S. dollar). Traditional econometric time series models were estimated using monthly data from January 2008 to December 2012 and the results allowed to infer that: i) increases in the dollar provide decreases in both taxes; ii) increases in the interest rate and restricted means of payment (M1) tend to provide increases in both taxes. Together, these results justify the concern and the need for intervention by the monetary authority in order to regulate the behavior of these controls.